The capital buffer paradox: Strong heterogeneity in profitability determinants between small and over capitalized banks in Indonesia - Baharuddin Baharuddin; Budi Krisnanto; Abdul Gafar Samalam; Muhammad Rizal (Priviet Social Sciences Journal, 2025)
The Indonesian banking sector faces a paradox of maintaining high capital buffers for stability while pursuing profitability amid digital disruption. This study examines the profitability determinants of conventional commercial banks, with a novel focus on testing the moderating role of the Capital Adequacy Ratio (CAR) in the loan-to-deposit ratio (LDR) and return on assets (ROA) relationship a mechanism hypothesized to explain previous empirical inconsistencies. Using quarterly panel data from 43 banks from Q1 2020 to Q3 2025 (989 observations) and a Fixed Effects model corrected with robust standard errors, the results reveal three key findings. First, the moderation hypothesis is rejected; high capital buffers do not significantly alter the impact of LDR on ROA. Second, operational efficiency (BOPO) proves to be the most consistent and dominant determinant of profitability. Most importantly, the key contribution lies in the discovery of sharp heterogeneity: traditional determinant models exhibit very strong explanatory power (R² = 66%) for small banks (CAR ≤ 25.1%) but fail to explain profitability for large, over capitalized banks (R² = 26.1%), where no traditional variables are significant. This demonstrates that profitability drivers evolve with bank scale, rendering one size fits all policy and strategic approaches ineffective. Consequently, regulators must implement differentiated macroprudential policies, while bank management should tailor core strategies based on their specific segment.